2014
DOI: 10.1128/aac.01884-13
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Modeling of the Unbound Levofloxacin Concentrations in Rat Plasma and Prostate Tissue Measured by Microdialysis

Abstract: bLevofloxacin is a broad-spectrum fluoroquinolone used in the treatment of both acute and chronic bacterial prostatitis. Currently, the treatment of bacterial prostatitis is still difficult, especially due to the poor distribution of many antimicrobials into the prostate, thus preventing the drug to reach effective interstitial concentrations at the infection site. Newer fluoroquinolones show a greater penetration into the prostate. In the present study, we compared the unbound levofloxacin prostate concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 33 publications
4
24
0
Order By: Relevance
“…No differences in the in vivo lung relative recovery were observed between healthy animals (11.3% Ϯ 1.9%) and infected animals (12.2% Ϯ 0.5%). The in vivo RR RD was lower than the recovery rate determined in vitro, which could be explained by tissue characteristics, such as tissue protein binding, blood flow, interstitial volume, and tissue tortuosity, as previously reported for other drugs (18,19). The in vivo recoveries were employed to calculate the true lung free levels, measured by microdialysis, in healthy and infected animals.…”
Section: Resultsmentioning
confidence: 82%
“…No differences in the in vivo lung relative recovery were observed between healthy animals (11.3% Ϯ 1.9%) and infected animals (12.2% Ϯ 0.5%). The in vivo RR RD was lower than the recovery rate determined in vitro, which could be explained by tissue characteristics, such as tissue protein binding, blood flow, interstitial volume, and tissue tortuosity, as previously reported for other drugs (18,19). The in vivo recoveries were employed to calculate the true lung free levels, measured by microdialysis, in healthy and infected animals.…”
Section: Resultsmentioning
confidence: 82%
“…Studies using D have demonstrated that antimicrobials may show differences between free plasma and free tissue concentrations when drug efflux and influx transporters contribute to distribution (19,20). Moreover, pathological conditions can change tissue-blood relationships, and antimicrobial concentrations in infected tissues may differ from those in healthy tissues due to increased temperature, decreased pH, plasma extravasations, and leukocyte migration at the infection site (18,21).…”
mentioning
confidence: 99%
“…However, measurements from tissue homogenates can overestimate drug concentrations at the target site, especially for fluoroquinolones that accumulate in the intracellular space (15). Although LEV demonstrated good tissue penetration in studies where free ISF concentrations were measured in human lung (16) and rodent prostate (17), the penetration factor (tissue bioavailability [fT tissue ]) determined by the relationship between the area under the concentration-time curve corresponding to free tissue exposure (AUC free,tissue ) and that corresponding to free plasma exposure (AUC free,plasma ) was lower than 100%. Furthermore, P-gp and other membrane transporters are involved in fluoroquinolone tissue distribution (18), and reports in the literature indicate that P-gp is expressed in lung and prostate (19,20).…”
mentioning
confidence: 99%
“…Our research group has been successfully applying microdialysis to analyze the tissue distribution of antifungal compounds (25,26) and antimicrobial compounds (27,28). Recently, we determined LEV prostatic penetration by microdialysis (17). The LEV prostate penetration factor (fT prostate ) value was 0.78, indicating that efflux transporters may be involved in this antimicrobial distribution process, reducing tissue levels.…”
mentioning
confidence: 99%